Analisis Literatur: Dinamika Komunikasi Keluarga Sebagai Fondasi Kesejahteraan Emosional Anak Usia Dini - Virgina Cahya Hardianto; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Early childhood represents a critical period for the development of long-term psychological well-being. This study aims to analyze how family communication dynamics serve as the primary foundation for a child's emotional welfare. Through a literature analysis of 19 relevant journal articles, it was found that open interpersonal communication, emotional validation, and the active involvement of both parents are key determinants of a child's resilience. Conversely, communication failures such as abusive parenting styles, the absence of a father figure (fatherlessness), and post-divorce conflict act as significant risk factors for mental health disorders. The synthesis results demonstrate that family communication is not merely an exchange of information, but an emotional support system that shapes a child's emotional intelligence and stress-coping abilities